Bioceramic Surface Topography Regulating Immune Osteogenesis - Jianxin Hao; Lin Du; Yuening He; Chengtie Wu (BME Frontiers)
Objective: This study aims to clarify the effects of bioceramic interface cues on macrophages. Impact Statement: Recently, there have been many researches exploring the effects of interface topography cues on macrophage polarization and cytokine secretion. However, the effects and underlying mechanisms of bioceramic interface cues on macrophages still need exploring. This study provides insights into the effects of bioceramic micro-groove surface structures on macrophages. Introduction: With the development of bone tissue engineering methods, bioceramics have been used for bone repair. After the implantation of bioceramics, innate immune response that occurs at the interface of materials can deeply influence the subsequent inflammation and bone regeneration progress. Therefore, the exploration and regulation of immune response of the bioceramic interface will be beneficial to promote the bone regeneration effects. Methods: In this study, bioceramics with micro-groove structures on the surface are fabricated by digital light processing 3-dimensional printing technology. Then, micro-groove structures with different spacings (0, 25, 50, and 75 μm) are prepared separately to explore the effects on macrophages. Results: The large spacing micro-groove structure can promote the M2 polarization and osteoinductive cytokine secretion of macrophage. The reason is that the large spacing micro-groove structure can induce directional arrangement of macrophage so as to change the phenotype and cytokine secretion. Further researches show that macrophage of the large spacing micro-groove structure can promote the osteogenic differentiation of bone mesenchymal stem cells, which can benefit osteogenesis and osteointegration. Conclusion: This study offers an effective and application potential method for bone repair.